Oczekiwania dotyczące własnej osoby i przyszłego partnera małżeńskiego w późnej adolescencji - Liberska, Hanna (Wydawnictwo Naukowe UAM, 2001)
The article has touched upon the problem o f young peoples expectations towards themselves and their future husbands / wives, as well as their selected conditioning. The results of the research carried out on 120 subjects, aged 16-20, have shown the differences of the above expectations as far as sex and some identity aspects are concerned. In general, among the youth egalitarian expectations in reference to their own life achievements and the achievements o f their partners prevail. Young people prefer partnership model of marriage, although this tendency is dominant among men.
Expectations of young people concerning themselves and their future partners in late adolescence